Reclaiming an Anti-Tin Mining Territory: The Effectiveness of Formal Political Channels in East Belitung - Bagus Sholihin, Eko (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
Tin, a mineral abundant beneath the coastal waters of Bangka Belitung, has spurred large-scale mining expansion from land to the sea. This article investigates the phenomenon of “reclaiming an anti-mining territory” as a representation of the Belitung community’s resistance against tin mining expansion into the coastal sea of East Belitung. The article is the result of deep fieldwork conducted during 2017-2020, employing methods such as participant observation and in-depth interviews with PT Timah, district and provincial government, local academics, resistance groups, local CSOs, fishermen, maritime tourist entrepreneurs, and traditional miners. This study reveals the limitations of the common argument that often raises scepticism about the accommodation and effectiveness of formal political channels for civil society resistance during conflicts over the expansion of extractive industries. Through a case study of the successful community resistance in East Belitung against the expansion of coastal tin mining, this article demonstrates that under certain preconditions—specifically, when “anti-sea mining” becomes a popular electoral issue— two specific key conditions can enable formal political channels to be effective: the recentralisation of mining authority and the formation of alliances with political elites. The findings further illustrate that zoning regulations, which were established in response to grassroots aspirations, were adhered to by all stakeholders, including licensed mining companies. These findings also present an opportunity for sustainable natural resource governance reform, particularly in terms of civic engagement in natural resources management.